Identification and Comparative Analysis of microRNA in Wheat (Triticum aestivum L.) Callus Derived from Mature and Immature Embryos during In vitro Culture - Chu, Zongli; Chen, Junying; Xu, Haixia; Dong, Zhongdong; Chen, Feng; Cui, Dangqun (Frontiers in Plant Science, 2016)
Feasible and efficient tissue culture plays an important role in plant genetic engineering. Wheat (Triticum aestivum L.) immature embryos (IMEs) are preferred for tissue culture to mature embryos (MEs) because IMEs easily generate embryogenic callus, producing large number of plants. The molecular mechanisms of regulation and the biological pathways involved in embryogenic callus formation in wheat remain unclear.Here, microRNAs (miRNAs) potentially involved in embryogenic callus formation and somatic embryogenesis were identified through deep sequencing of small RNAs (sRNAs) and analyzed with bioinformatics tools. Six sRNA libraries derived from calli of IMEs and MEs after 3 d, 6 d, or 15 d of culture (DC) were constructed and sequenced. A total of 85 known miRNAs were identified, of which 30, 33, and 18 were differentially expressed (P< 0.05) between the IME and ME libraries at 3 DC, 6 DC, and 15 DC, respectively. Additionally, 171 novel and 41 candidate miRNAs were also identified, of the novel miRNA, 69, 67, and 37 were differentially expressed (P< 0.05) between the two types of libraries at 3 DC, 6 DC, and 15 DC, respectively. The expression patterns of eight known and eight novel miRNAs were validated using quantitative real-time polymerase chain reaction. Gene ontology annotation of differentially expressed miRNA targets provided information regarding the underlying molecular functions, biological processes, and cellular components involved in embryogenic callus development. Functional miRNAs, such as miR156, miR164, miR1432, miR398, and miR397, differentially expressed in IMEs and MEs might be related to embryogenic callus formation and somatic embryogenesis. This study suggests that miRNA plays an important role in embryogenic callus formation and somatic embryogenesis in wheat, and our data provide a useful resource for further research.